Determinants of Nile tilapia’s (Oreochromis niloticus) growth in aquaculture pond in Batu, Indonesia - Evellin Dewi Lusiana; Muhammad Musa; Syahril Ramadhan (Society for Indonesian Biodiversity, 2021)
Abstract. Lusiana ED, Musa M, Ramadhan S. 2021. Determinants of Nile tilapia’s (Oreochromis niloticus) growth in aquaculture pond in Batu, Indonesia. Biodiversitas 22: 999-1005. Nile tilapia (Oreochromis niloticus) has been commonly cultured all over the world, especially in Indonesia, due to high market demand. The success of Nile tilapia culture production depends on the fish growth during cultivation as well as pond environment. Many studies have revealed that quality of water strongly affects fish growth in an aquaculture pond. This study aims to investigate the relationship among water quality like Physico-chemical (temperature, transparency, pH, dissolved oxygen, carbon dioxide, nitrate, and phosphate) and biological (phytoplankton abundance) factors and the specific growth rate of Nile tilapia in a freshwater cultivation pond in Batu City, Indonesia. The data was analyzed using the path model. Results indicated that the most significant factor for fish growth was the phytoplankton abundance. However, since nitrate and phosphate also played roles as determinants of phytoplankton abundance, they can be considered indirect water quality factors of Nile tilapia growth.